An efficient group key agreement protocol for secure P2P communication. Issue 17 (22nd August 2016) - Vijayakumar, Pandi; Naresh, Ramu; Jegatha Deborah, Lazarus; Hafizul Islam, SK
Abstract: The efficient design of a distributed group key management for a peer to peer (P2P) network with minimal computation complexity in dynamic secure group communication is a challenging issue. This is because of the absence of a centralized coordinator. In order to provide this facility, a self‐composed distributed group key management framework is proposed for secure P2P communication. In this proposed work, group key computation is performed using Chinese remainder theorem and secure communication is performed through RSA encryption algorithm. This self‐composed key management is a one round protocol in which a shared group key is generated using the public key of each individual user, and it is derived from the respective private key. The main advantage of the group key management scheme proposed in this paper is that it reduces the computation complexity of the peer users to O (1). This reduction in computation complexity is achieved by performing one addition and multiplication operation during a single member join and one subtraction operation during a single member leave operation. The proposed algorithm has been implemented and analyzed with well‐known existing distributed group key management protocols and observed that it reduces the computation complexity significantly. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A computation efficient self‐composed group key agreement protocol is proposed in this research paper to perform dynamic secure group communication in peer‐to‐peer network.